THE IMPACT OF THE COVID-19 PANDEMIC ON TEACHING AND LEARNING PROCESS; REVIEW RESEARCH - Moh.Heru Budihantho, Sari Listyorini, Halim Dwi Putra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study became to select out acquiring data on the restrictions of the teaching and learning technique on-line reception as a result of the presence of a COVID-19 pandemic. they need a glance at used an exploratory case to observe method and therefore the studies approach used a qualitative case observe technique wont to reap information on the restrictions and results of the COVID-19 pandemic towards teaching and learning activities in primary faculties. during this study, respondents are 50 lecturers and 150 students in Malang-East Java. For confidentiality purposes, respondents are given initials. Semi-dependent interviews are administered and an inventory of questions compiled for interviews was developed based on the associated literature. Respondents for this look are 50 teachers and 150 students in numerous campuses in Malang. the results of this study are that there are numerous limitations skilled via teachers and college students in online teaching and learning activities, particularly mastery of technology remains missing, additional internet quota costs, there are additional jobs for lecturers and students within the teaching and learning procedure.